2010
DOI: 10.1115/1.3103926
|View full text |Cite
|
Sign up to set email alerts
|

Improving Efficiency of a High Work Turbine Using Nonaxisymmetric Endwalls—Part II: Time-Resolved Flow Physics

Abstract: This paper is the second part of a two part paper that reports on the improvement of efficiency of a one and a half stage high work axial flow turbine. The first part covered the design of the endwall profiling, as well as a comparison with steady probe data; this part covers the analysis of the time-resolved flow physics. The focus is on the time-resolved flow physics that leads to a total-to-total stage efficiency improvement of 1.0%±0.4%. The investigated geometry is a model of a high work (Δh/U2=2.36), axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Schuepbach et al [16] confirmed these efficiency improvements by a time-resolved experimental and numerical investigation of the flow physics, which highlighted the presence of reduced blade trailing edge shed vorticity in the contoured wall passage.…”
Section: Introductionmentioning
confidence: 84%
“…Schuepbach et al [16] confirmed these efficiency improvements by a time-resolved experimental and numerical investigation of the flow physics, which highlighted the presence of reduced blade trailing edge shed vorticity in the contoured wall passage.…”
Section: Introductionmentioning
confidence: 84%
“…Experimental validation by Hartland et al [11] found a 30% reduction in aerodynamic losses for the contoured wall relative to a flat wall. Endwall contouring in the studies of Germain et al [12] and Schuepbach et al [13] produced an overall stage efficiency improvement of 1.0% 6 0.4% in a 1-1/2 stage turbine, which was largely attributed to reductions in the stator time-averaged and unsteady losses. Praisner et al [14] designed a nonaxisymmetric endwall contour based on secondary loss reduction metrics for the airfoil in this study.…”
Section: Relevant Past Studiesmentioning
confidence: 95%
“…16 and Schüpbach et al. 17 designed NAEP for a turbine by using an automatic numerical optimization method, which resulted in reduced secondary flow and an improvement of stage efficiency by 1% ± 0.4%. Poehler et al.…”
Section: Introductionmentioning
confidence: 99%